Understanding the Association of Sleep Disorders with Nursing Productivity in Malaysia - Anuar, Annurizal; Othman, Abdul Kadir; Maon, Siti Noorsuriani; Dzulkipli, Mohd Redhuan; Abdullah, Mohd Zulkifli; Abdul Rahim, Ramita (Information Management and Business Review, 2023)
This study examines the relationship between sleep disorders and productivity, specifically absenteeism and presenteeism, among nurses in Malaysia. The research objective is to assess the impact of sleep disorders on nurses’ productivity by analyzing their absenteeism and presenteeism levels. This present study is correlational in design since it is intended to describe the relationship between sleeping disorders and nurses’ productivity. The study used stratified sampling to select the respondents from two private hospitals. The list of nurses was provided by the hospital management to facilitate the selection process. The questionnaire was personally distributed to the selected employees by the researchers. At the end of the data collection period, a total of 200 sets of the questionnaire were received, indicating a 100% response rate. The study’s contribution lies in adding to the understanding of the crucial link between sleep disorders and productivity in the nursing profession. By emphasizing the adverse effects of sleep disturbances on nurses’ efficiency, the research underscores the importance of targeted interventions and policy measures to support healthcare professionals’ well-being and productivity. The implications extend to healthcare management and policymakers, urging them to prioritize sleep health and consider strategies that mitigate the impact of sleep disorders on nursing staff. To advance this field, future research should focus on larger sample sizes and diverse populations to comprehensively explore the broader implications of sleep disorders on productivity. Such studies can lead to more effective measures for improving the work environment, reducing absenteeism, and enhancing overall patient care and outcomes.